Regional Impacts of Liberalization of Barriers against Foreign Direct Investment in Services: The Case of Russia's Accession to the WTO - Rutherford, Thomas F.; Tarr, David G. (2012)
In this paper, the authors develop a 10-region comparative static computable general-equilibrium model of Russia to assess the impact of accession to the World Trade Organization on the regions of Russia. The model allows for foreign direct investment in business services and endogenous productivity effects from additional varieties of business services and goods produced under imperfect competition. The authors then show that these features are crucial to the results, as the welfare gains are about 20 times greater than in a constant-returns-to-scale model. The results for the estimated gains vary considerably across the regions; this is principally explained by the ability of the different regions to benefit from a reduction in barriers against foreign direct investment.